Pembelajaran Matematika dengan Metode Accelerated Learning untuk Meningkatkan Kemampuan Penalaran Adaptif - Putra, Rizki Wahyu Yunian (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
The ability of adaptive reasoning is a competence that must be possessed by students, but the reality of the field shows that students' adaptive reasoning ability is still not satisfactory. Learning with the accelerated learning method is applied in the hope of improving students' adaptive reasoning abilities. The purpose of this research is to know whether the improvement in students' adaptive reasoning ability with accelerated learning method is better than ordinary learning. This research is a quasi-experiment or quasi-experiment with pretest-posttest control group design. Implementation of this research is done on grade VIII students in one of the State Junior High School in Bandar Lampung. Problems given are questions of reasoning ability of adaptive in material relation and a function, test of ability, ability of reasoning is tested theoretically by validating with picture that test question can be well understood and empirically validity and reliability fulfill characteristic to be used in research, The degree of difficulty and distinguishing power of the problem can already be used to determine the enhancement of the ability of adaptive reasoning. Quantitative data analysis was performed using flat most different and N-Gain test. The results of this study are students whose learning to apply learning with an accelerated learning method of enhancing the ability of adaptive reasoning is significantly better than that of students whose learning using ordinary learning is reviewed in whole.